HARMONISASI PENGATURAN TENTANG PENERBITAN OBLIGASI DAERAH SEBAGAI SALAH SATU SARANA INVESTASI BAGI MASYARAKAT DAN SUMBER PENDANAAN BAGI PEMERINTAH DAERAH - Saragih, Rudolf Valentino; Tumanggor, M.S.; Simanjuntak, Nelson (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2021)
Municipal bonds are debt securities issued by local governments that are offered to the public through public offerings on the capital market. The issuance of debt securities is evidence that the local government has made a loan or debt to the holders of the debt securities. The choice to develop municipal bonds is based on the small development budget in the regions which makes public services neglected. In addition, there is a trend of capital spending in the APBD that does not support development and provision of infrastructure that supports economic development. On the other hand, regional loans in developed countries have become a trend of sources of financing for infrastructure development, for example in Vietnam, China, Japan and other countries. In the national context, Indonesia’s status as a middle income country makes it increasingly difficult for Indonesia to obtain soft or cheap loans from international donor agencies and from bilateral countries. However, local governments in issuing regional bonds on the capital market, there are obstacles in terms of regulations, including the approval of the DPRD and the obligation to audit regional finances by public accountants. Therefore it is interesting to do research, using normative juridical research methods with descriptive analytical. Keywords: Harmonization; Investment; Municipal Bond; Regional Government